1990
DOI: 10.1111/j.1469-7610.1990.tb00800.x
|View full text |Cite
|
Sign up to set email alerts
|

Screening Measures for Detecting Psychiatric Disorders in Japanese Secondary School Children

Abstract: Measurement characteristics of screening measures (Rutter's teachers' and parents' questionnaires) were explored with some Japanese secondary school children. The characteristics included stability, cut-off points, factor analyses and agreements between questionnaire diagnoses and interviewer's judgement concerning types of disorder. These measures were used in combination and checked in terms of measurement characteristics. Age trends in the obtained results were described using 12-13-yr-old and 14-15-yr-old … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
27
0

Year Published

1996
1996
2004
2004

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 27 publications
(33 citation statements)
references
References 16 publications
6
27
0
Order By: Relevance
“…Their explanatory powers are moderate but the factors were robust as different statistical rotation methods and raters did not alter the factor structures, and they have fairly high internal consistency. The findings are in line with those reported by McGee et al (1985) in New Zealand, Morita et al (1990) in Japan, and Taylor et al (1991) in United Kingdom. These findings lend support to the existence of a construct of hyperactivity, apart from antisocial and emotional disturbances, across different cultures.…”
Section: Discussionsupporting
confidence: 95%
See 3 more Smart Citations
“…Their explanatory powers are moderate but the factors were robust as different statistical rotation methods and raters did not alter the factor structures, and they have fairly high internal consistency. The findings are in line with those reported by McGee et al (1985) in New Zealand, Morita et al (1990) in Japan, and Taylor et al (1991) in United Kingdom. These findings lend support to the existence of a construct of hyperactivity, apart from antisocial and emotional disturbances, across different cultures.…”
Section: Discussionsupporting
confidence: 95%
“…Morita et al (1990) in Japan reported a similar phenomenon in which disobedience had the lowest factor loading (0.50 vs. 0.74 to 0.84) on the Hyperactivity factor. This finding is not evident in studies in the West.…”
Section: Discussionsupporting
confidence: 49%
See 2 more Smart Citations
“…10 Four of the factors relating to conduct problems, hyperactivity, school problems and emotional problems are similar to those obtained in this study. The Japanese study involved interviewing children judged as having deviant behaviour by a school nurse, thus indicating a high level of psychopathology in the sample.…”
Section: Discussionsupporting
confidence: 83%